We can simplify this expression by using the properties of exponents.
When dividing with exponents, we subtract the exponents:
4^13 ÷ 3^(-5) = 4^13 × 3^5
Next, we can rewrite 3^5 as (3^(-5))^-1 since any number raised to the -1 power is the reciprocal of the number:
4^13 × (3^(-5))^-1
Now, apply the power rule of exponents, which states that when raising a power to a power, we multiply the exponents:
4^13 × 3^(-5)(-1)
= 4^13 × 3^(-5) × 3^(-1)
= 4^13 × 3^(-6)
= 4^13/3^6.
Therefore, the simplified expression is 4^13/3^6.
Simplify 4^13÷3^−5.
1 answer